Peran Orang Tua dalam Mendampingi Anak Belajar Selama Pandemi - Eko Hari Purnomo; Tutuk Ningsih (Jurnal Kependidikan, 2020)
Abstract Government policy in the world of education during the pandemic requires teaching and learning activities to no longer be in schools, but to be diverted into distance learning activities for safety and health that are centered in their homes. Situations and conditions like this require the maximum involvement of parents and restore the role of parents in educating children essentially. The role and function of parents initially is as a place for children's education to be first and foremost in instilling religious values, shaping character and character, but during a pandemic like this where children have to study at home, the role of parents increases by accompanying children when learning is something very important. The purpose of this study is to describe and analyze the role of parents in accompanying children to learn during the pandemic. Data collection in the form of interviews, documentation, observation. And the type of research is qualitative. The results of research on the role of parents in accompanying children during the pandemic show that parents are very bothered in dividing their time, energy, and smartphone. From the research results, it can be concluded that parents have a very important role in assisting children to learn during a pandemic. Learning assistance for children can be seen from explaining material that the child does not understand, how parents help children's task difficulties, communicating or borrowing a smartphone to do the tasks given by the teacher. Keywords: Role of Parents, Learning Assistance, Pandemic. Abstrak Kebijakan pemerintah dalam dunia pendidikan saat pandemi mengharuskan kegiatan belajar mengajar tidak lagi di sekolah, namun dialihkan menjadi kegiatan pembelajaran jarak jauh demi keamanan dan kesehatan yang berpusat di rumah masing-masing. Situasi dan kondisi seperti ini mengharuskan interaksimorang tua secara lebihmmaksimal dan mengembalikan peran orang tua didalam mendidik anak secara hakiki. Peran dan fungsi orang tua awalnya adalah sebagai,tempat,pendidikan,anak,yang,pertama,dan,utama,didalam menanamkan nilai-nilai,,agama, membentuk karakter dan berbudi pekerti,meskipun saat terjadi pandemi seperti ini,,dimana anak harus belajar di rumah maka peran orang tua menjadi bertambah dengan mengawasi anak saat belajar merupakan hal yang begitu penting. Tujuan penelitian ini ingin mendiskripsikan dan menganalisa anak belajar dengan didampingi orang tua dalam pandemik. Wawancara, dokumentasi, dan observasi merupakan pengumpulan data. Serta jenis penelitian yaitu kualitatif. Hasil penelitian tentang anak dalam pandemic dengan didampingi oleh orang tua, menunjukkan bahwa orang tua begitu repot didalam membagi waktu, tenaga, dan smartphonnya. Dari hasil penelitian dapat disimpulkan bahwa orang tua memiliki peran yang sangat penting dalam mendampingi anak untuk belajar pada saat pandemi. Bantuan belajar anak terlihat dari penjelaskan tugas yang kurang dipahami anak, bagaimana orang tua membantu anak dengan tugas yang sulit, mengkomunikasikan atau peminjamkan smartphone untuk mengerjakan tugas yang diberikan oleh gurunya. Kata Kunci : PeranmOrangTua, Pendampingan Belajar, Pandemik.